The Difference of Oral Reading and Writing of Tiociu Languag - Lily Thamrin (Lingua Cultura, 2013)
Article presented the difference of oral reading and writing of TioCiu Guangdong Language, Tiongkok. The language is divided by its oral and writing regulation consisting of three factors: consonant, vocal, and tone, as well as the description of different TioCiu reading dialect. Article focused on the analysis and description of the oral reading and the writing of TioCiu language, which is divided into two parts: the TioCiu phonetic system and the different regulation of oral reading and TioCiu writing. It can be concluded that the different reading of oral and writing of TioCiu language is mostly shown in the consonant pronunciation, whereas the vocal pronunciation less happened.